Pengaruh lama ketiadaan inang terhadap kapasitas reproduksi parasitoid Snellenius manilae Ashmead (Hymenoptera: Braconidae) - Mohamad Eldiary Akbar; Damayanti Buchori (Jurnal Entomologi Indonesia, 2012)
The objective of this research was to study the  influence  of host deprivation on the oviposition and physiological condition of Snellenius manilae Ashmead. The research was conducted at Laboratory of Bioecology of Parasitoid and Predator, Department of Plant Protection, Faculty of Agriculture, IPB. Ten parasitoids of the same age and cohort were used in this experiment. Deprivation of hosts were done for 1, 2, 3, 4, 5, 6 and 7 days at the beginning and toward the end of their life. All hosts were replaced every 24 hours. Result indicated that host deprivation affects the reproductive capacity of Snellenius manilae. Even though parasitoids were able to lay eggs even when they were deprived of hosts for seven consecutive days, the overall results of host deprivation experiment showed that the length and timing of deprivation period can affect reproductive capacity. Deprivation of hosts tends to increase the parasitism rate and the numbers of eggs laid upon their first encounter of hosts after the treatment. The difference is more pronounced on treatements that allowed parasitism to occur before the deprivation treatment. However, the overall results suggests that deprivation overall decrease the reproductive capacity of the parasitoid. The longevity of deprived individuals was also lengthened. Parasitoids that were given host before deprivation treatments tend to produced more eggs than those were not. These results showed that deprivation of hosts in the field may affect the effectiveness of parasitoids and the success of biological control.